Conservation of Endophyte Bacterial Community Structure Across Two Panicum Grass Species - Singer, Esther; Bonnette, Jason; Woyke, Tanja; Juenger, Thomas E. (Frontiers in Microbiology, 2019)
Panicum represents a large genus of 100s of North American prairie grass species. These include switchgrass (Panicum virgatum), a biofuel crop candidate with wide geographic range, as well as Panicum hallii, a close relative to switchgrass, which serves as a model system for the study of Panicum genetics due to its diploid genome and short growth cycles. For the advancement of switchgrass as a biofuel crop, it is essential to understand host microbiome interactions, which can be impacted by plant genetics and environmental factors inducing ecotype-specific phenotypic traits. We here compared rhizosphere and root endosphere microbial communities of up- and lowland P. virgatum and P. hallii genotypes planted at two sites in Texas. Our analysis shows that sampling site contributed to most microbial community variability in the rhizosphere, however, impacted root endosphere microbial communities much less. Instead we observed a relatively large core endophytic microbiome dominated by universal root colonizing bacteria Streptomyces, Pseudomonas, and Bradyrhizobium. Endosphere communities displayed comparable diversity and conserved community structures across genotypes of both Panicum species. Functional insights into interactions between P. hallii and its root endophyte microbiome can hence inform testable hypotheses that are relevant for the improvement of switchgrass as a biofuel crop.